Seasoning Funnels Die Design for Autopacking Machine Distributors Using SUS 316 Material - Jatira Jatira; Amri Abdulah; Sukarman Sukarman; Apang Djafar Shieddique; Dede Ardi Rajab; Satria Prayoga (Jurnal POLIMESIN, 2022)
This article discussed the design of dies and punches using SUS 316 material for seasoning funnel (SF) applications in the food industry. Cracks in the welding zone in the seasoning funnel (SF) result in leakage of seasonings and result in product mass, which is one of the main parameters in the food industry and a minimum. The damage location on the SF is identical, on the sides of the SF around the bolt holes. The movement of the spice powder, which rotates at high speed, produces a centrifugal force and is then transferred through the SF. The metal structure is becoming increasingly coarser in the area adjacent to the weld melting line. An additional punch with a knocking arm delivers to the SF to expedite the transfer. The knocking arm caused the SF fracture on the SF. SUS 316 sheet metal material for SF without welding is thought to reduce weld damage and speed up the procurement process. The input design for attempting to make dies has been correctly selected as SUS 316 material thickness of 1.0 mm. The two main processes required to form SF from sheet metal were blanking and bending. The SKD-11 material was selected carefully for the main components of the dies and punch. Supporting components such as shank, shaft, top plate, and bottom plate are determined using St 60 material. St 37 material determines the stripper, punch holder, and stopper components. Based on theoretical calculations, the blanking force should be about 225.5 kN. To minimize the burr in the blanking process, dies and punch allowances of 0.1 mm were chosen. The minimum required bending force calculation was 39 kN. A material factor spring back value of 0.98 was selected correctly to achieve the desired bending angle. The simultaneous blanking and bending processes necessitated using a 72.96-tonne power press machine.